2010
DOI: 10.3892/ijo_00000727
|View full text |Cite
|
Sign up to set email alerts
|

Novel bladder preservation therapy for locally invasive bladder cancer: Combined therapy using balloon-occluded arterial infusion of anticancer agent and hemodialysis with concurrent radiation

Abstract: Abstract.We investigated the effect of balloon-occluded arterial infusion (BOAI) of anticancer agent (cisplatin/gemcitabine), used concomitantly with hemodialysis, which delivers an extremely high concentration of anticancer agent to the site of a tumor without systemic adverse effects, along with concurrent radiation (referred to as the OMC-regimen) in patients with advanced bladder cancer. One hundred and ninety-two patients were assigned to receive either the OMCregimen (n=96) or total cystectomy (n=96). Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 22 publications
0
32
0
2
Order By: Relevance
“…27,28 Several groups incorporated IAC into the trimodality protocol ( Table 2). CRT incorporating IAC produced high CR rates of 76-93%, [29][30][31][32] which could be attributed to a high drug concentration at the primary lesion, with OS and BIS equivalent to those of conventional CRT regimens. However, IAC results in a unique complication, pelvic neuropathy, with an incidence of 20-30%.…”
Section: Trimodality Bladder-sparing Therapymentioning
confidence: 97%
See 1 more Smart Citation
“…27,28 Several groups incorporated IAC into the trimodality protocol ( Table 2). CRT incorporating IAC produced high CR rates of 76-93%, [29][30][31][32] which could be attributed to a high drug concentration at the primary lesion, with OS and BIS equivalent to those of conventional CRT regimens. However, IAC results in a unique complication, pelvic neuropathy, with an incidence of 20-30%.…”
Section: Trimodality Bladder-sparing Therapymentioning
confidence: 97%
“…32 The regimen consisted of conformal radiation at 60.4 Gy with balloon-occluded IAC with high-dose cisplatin (100-300 mg as a single bolus). Hemodialysis was combined through two double-lumen catheters placed in the bilateral common iliac vein to reduce IACrelated toxicities.…”
Section: Intensification Of Concomitant or Adjuvant Chemotherapymentioning
confidence: 99%
“…A study of intra-arterial chemotherapy with 40 Gy of radiotherapy for pT1G3 bladder cancer for 11 patients seems to compare favourably with conventional treatments after short follow-up [48]. Most recently, Azuma et al [49 ] have reported on treatments undertaken between 1998 and 2008. Concurrent radiotherapy (60.4 Gy) with intraarterial cisplatin/gemcitabine and haemodialysis, a complex arrangement of pelvic catheters was used to deliver and retrieve the chemotherepeutic agents to maximize tumour dose while minimizing systemic exposure.…”
Section: Developments In Radiotherapy Technique For Muscle-invasive Bmentioning
confidence: 97%
“…Associée à la radiothérapie, elle est à l'origine d'un taux de réponse complète de 76 à 93 % avec cependant un taux élevé de neuropathie pelvienne pouvant atteindre les 20 à 30 % [112][113][114][115]. Dans la série d'Azuma et al, les dossiers de 96 patients ayant eu une cystectomie radicale ont été comparé rétrospectivement à ceux de 92 autres non candidats à une chirurgie ou la refusant et ayant eu une radiothérapie associée à une chimiothérapie intra-artérielle.…”
Section: En Chimiothérapieunclassified
“…Le groupe irradié comportait plus de patients avec un indice de performance faible, plus de tumeurs de haut grade, et plus de tumeurs de stade T4 ou N1, mais malgré ce biais de sélection, le taux de survie à 5 et à 15 ans était en faveur de la radiothérapie : 91 % et 81 % contre 60 % et 40 %. Aucune toxicité de grade 3 ou plus n'a été observée [115].…”
Section: En Chimiothérapieunclassified